A Bibliometric Analysis of Political Science Research on a Global Scale - Emre Aydilek (Akademik İncelemeler Dergisi)
This research aims to contribute to a macro-level understanding of the intellectual foundations of the field of political science by examining it in depth through bibliometric analysis and discovering the epistemological insights hidden in it, as well as the basic dimensions of studies in the discipline. Thus, it is objectives to provide basic data and guidance to academics working on the methodology of the discipline of political science. Accordingly, the trends, topics, and general themes of academic studies published in universally respected journals with high-impact factors in the field of political science will be identified. The article's original value is the first thorough bibliometric study of the discipline in Turkish national literature and one of the first few thorough bibliometric studies in international literature. This study conducted a brief literature review to examine key scientific texts on political science methodology that reflect general trends. Subsequently, data retrieved from two selected databases (Scopus and WoS) were analyzed and interpreted using text-mining tools (WOSviewer and R Studio). As a result of this analysis, 17 datasets and meaningful patterns emerged. Word clouds, bibliometric maps, heat maps, and word maps were obtained, which include the analysis of studies according to years, fields, types, impact values, factors, themes, trends, and countries with the most studies. The findings are interpreted in the conclusion, and a general trend in the discipline is presented.